Mexican lithium: from its “nationalization” to the dispute with China - Rodríguez, Violeta Núñez (Geografares, 2026)
This article analyzes the growing global demand for lithium, emphasizing its use in electric batteries, which account for nearly 90% of consumption. It examines strategic territories, including Bolivia, Argentina, Chile, Mexico, Brazil, and Peru, which collectively hold the world’s largest lithium resources. Specifically, the study focuses on Mexico. Given its lithium wealth—ranking tenth globally—former President López Obrador declared lithium a strategic element and national heritage. This measure sought to protect the resource by preventing the granting of mining concessions to private companies, which had previously seized more than half of the national territory. Nevertheless, a Chinese company has sued the Mexican government to exploit Mexico’s lithium. The corporation had proposed exporting the raw clay to Asia without domestic processing. Such practices perpetuate permanent primary accumulation, accumulation by dispossession, the primary-export model, and necroeconomics.